Conformational Entropy as a Means to Control the Behavior of Poly(diketoenamine) Vitrimers In and Out of Equilibrium. (21st November 2019) - He, Changfei; Christensen, Peter R.; Seguin, Trevor J.; Dailing, Eric A.; Wood, Brandon M.; Walde, Rebecca K.; Persson, Kristin A.; Russell, Thomas P.; Helms, Brett A.
Abstract: Control of equilibrium and non‐equilibrium thermomechanical behavior of poly(diketoenamine) vitrimers is shown by incorporating linear polymer segments varying in molecular weight (MW) and conformational degrees of freedom into the dynamic covalent network. While increasing MW of linear segments yields a lower storage modulus at the rubbery plateau after softening above the glass transition (Tg ), both Tg and the characteristic time of stress relaxation are independently governed by the conformational entropy of the embodied linear segments. Activation energies for bond exchange in the solid state are lower for networks incorporating flexible chains; the network topology freezing temperature decreases with increasing MW of flexible linear segments but increases with increasing MW of stiff segments. Vitrimer reconfigurability is therefore influenced not only by the energetics of bond exchange for a given network density, but also the entropy of polymer chains within the network. Abstract : Entropisches Klima : Mikrostrukturelle und Architektur‐Attribute von Vitrimeren sind leistungsfähige Gestaltungselemente für die Kontrolle ihrer mechanischen und rheologischen Eigenschaften. Die Konformationsentropie ihrer Monomersegmente dominiert anscheinend diese Eigenschaften in ähnlich aufgebauten Vitrimer‐Netzwerken.